Raising a Child with Intellectual Disability: Parental Stress and Coping - P, Neha Sunil; P. J, Dr. Lizy; C, Dr. Sunitha Srinivas (Migration Letters, 2024)
The disability of a child is a triadic experience involving three-way interactions between the child experiencing the dysfunction, the family affected by the dysfunction, and the outer environment where the disability is manifested (Falik, 1995). Parenting is a hard job, so having a disabled child will make things more difficult. Given that children with disabilities have impaired physical-psycho-social development, parents can find their roles very stressful when dealing with developmental issues that result in social, economic/financial problems, as well as physical and psychological problems (Hartley, Barker, Seltzer, Floyd, Greenberg, Orsmond & Bolt, 2010). Children’s disabilities may burden their family members, especially their parents, who are their long-term caregivers. Though many studies describe and document concerns, problems, or worries that disabled children face, there were no published studies that were carried out for parents with a child with a severe intellectual disability. In India, especially in Kerala, hardly any studies are done in the area of parents of children who have a severe intellectual disability. This paper has developed from a study conducted by the author with the prime purpose of identifying the level of stress experienced by parents of children with Severe Intellectual Disabilities in Special schools in Calicut district, the coping strategies adopted by them to deal with stress, and the effect of gender and the level of education of parents on their stress levels and coping. A total of 60 parents, both fathers and mothers, were included in the study (30 fathers and 30 mothers). The statistical test employed was a two-way ANOVA to find out the significant difference between gender and educational level on the level of stress and coping. The results obtained from the analysis showed that the relationship between parental stress and coping was negative and highly significant.